2018
DOI: 10.5194/acp-18-16033-2018
|View full text |Cite
|
Sign up to set email alerts
|

Global streamflow and flood response to stratospheric aerosol geoengineering

Abstract: Abstract. Flood risk is projected to increase under future warming climates due to an enhanced hydrological cycle. Solar geoengineering is known to reduce precipitation and slow down the hydrological cycle and may therefore be expected to offset increased flood risk. We examine this hypothesis using streamflow and river discharge responses to Representative Concentration Pathway 4.5 (RCP4.5) and the Geoengineering Model Intercomparison Project (GeoMIP) G4 scenarios. Compared with RCP4.5, streamflow on the west… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 112 publications
(170 reference statements)
2
15
0
Order By: Relevance
“…A sustained layer of additional sulfate aerosols in the stratosphere would scatter some of the incoming solar radiation back to space, cooling the Earth. Numerous climate modeling studies on SAG have suggested that it could reduce many impacts of anthropogenic global warming, such as sea level rise, floods, permafrost degradation, and extreme weather (e.g., Rasch et al, ; Moore et al, ; Irvine et al, ; Wei et al, ; Ji et al, ; Lee et al, ), and also have side effects such as decreased stratospheric ozone concentrations in polar regions (Pitari et al, ; Tilmes et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A sustained layer of additional sulfate aerosols in the stratosphere would scatter some of the incoming solar radiation back to space, cooling the Earth. Numerous climate modeling studies on SAG have suggested that it could reduce many impacts of anthropogenic global warming, such as sea level rise, floods, permafrost degradation, and extreme weather (e.g., Rasch et al, ; Moore et al, ; Irvine et al, ; Wei et al, ; Ji et al, ; Lee et al, ), and also have side effects such as decreased stratospheric ozone concentrations in polar regions (Pitari et al, ; Tilmes et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Such pattern resembles the present analysis of HadGEM2-ES. Wei et al (2018) analyzed the changes in global streamflow and flood return periods under the GeoMIP G4 scenario. Although it is not clear how the drought/flood pattern will respond over East Asia when geoengineering is employed, the aforementioned risk should be considered.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Simulations of global climate models show that the three RFGs have enough potential to lower the representative concentration pathway 8.5 (RCP8.5) global warming level to a warming level similar to that under RCP4.5 and even to a 1.5°C warming threshold (Kravitz et al, 2015;MacMartin et al, 2018). In contrast to their consistent cooling potentials, individual RFGs induce different impacts on the Earth's large-scale circulation, raising concerns over inequality risks of RFG impacts on regional climate and hydrological cycle (Crook et al, 2015;Irvine et al, 2010;Irvine et al, 2019;Wei et al, 2018), as well as the distribution and dynamics of climate regimes, such as drylands. Many assessments have examined the potential of RFGs to induce changes in the regional climate, especially precipitation (P) (Kristjánsson et al, 2015;Niemeier et al, 2013;Stjern et al, 2018), but the response of drylands to individual RFGs remains unexplored.…”
Section: Citationmentioning
confidence: 99%